THE CONTRACT RELAX STRETCHING LEBIH EFEKTIF MENINGKATKAN FLEKSIBILITAS OTOT HAMSTRING DIBANDINGKAN DENGAN PASSIVE STRETCHING PADA ATLET UNDERDOG TAEKWONDO CLUB - Wiguna, Arya; Silakarma, Dedi; Sundari, Ratna (Majalah Ilmiah Fisioterapi Indonesia, 2015)
Flexibility is one of the components needed at any athlete especially taekwondo athletes. To increase the flexibility stretching methods were used. This research use contract relax stretching and passive stretching to increased hamstring muscle flexibility.This research was implemented from May up to June 2014 in Golkar Building, Puputan, Bali which use sit and reach test instrument to measure hamstring muscle flexibility.This research is an eksperimental research and the design used in this study design was two groups pre and post design, consisting of a 1th treatment group and the 2nd treatment group, with random sampling, the total sample is 24 subjects and divided into 2 groups, the 1th treatment group receive contract relax stretching while the 2nd treatment group receive passive stretching.The result of this research is increased flexibility in the 1st treatment group with p =0.000 (p<0.05), and increased flexibility in the 2nd treatment group with p=0.000 (p<0.05), once compared the 1st treatment group and the 2nd treatment group p=0.000 (p<0.05), where is from this research result the two groups have increased hamstring muscle flexibility however increased flexibility in 1st treatment group is more effective than 2nd treatment group. From this research it can be concluded that contract relax stretching is more effective to increases flexibility hamstring muscle compared with passive stretching.
Keywords: hamstring muscle flexibility, contract relax stretching, passive stretching.